106 Endogenous synthesis of amino acids is insufficient for animal lactation, reproduction and growth. (7th December 2018) - Wu, G
Abstract: Research in the early 1990s reporting high abundances of glutamine and glutamate but severe deficiencies of arginine and glycine in sow's milk led to extensive studies over the past two decades that establish dietary needs of animals for synthesizable amino acids (AA). Based on growth or nitrogen balance, AA had traditionally been classified as nutritionally essential (EAA) or nonessential (NEAA) for animals. Essential AA are defined as either those AA whose carbon skeletons cannot be synthesized de novo in animal cells or those that normally are insufficiently synthesized de novo by the animal organism relative to its needs for maintenance and growth and which must be provided in the diet to meet requirements. In contrast, NEAA are those AA which can be synthesized de novo in adequate amounts by the animal organism to meet its requirements for maintenance and growth and, therefore, need not be provided in the diet. The content of NEAA in the body is much greater than that of EAA. Although EAA and NEAA had been described for over a century, no compelling data indicate that NEAA are synthesized sufficiently in animals to meet their metabolic needs for maximal growth and optimal health. NEAA play important roles in regulating gene expression, cell signaling pathways, digestion and absorption of dietary nutrients, DNA and protein synthesis, metabolism of glucose and lipids, endocrine status, male and female fertility, acid-base balance, antioxidative responses, detoxification of xenobiotics and endogenous metabolites, neurotransmission, and immunity. Emerging evidence indicates dietary essentiality of NEAA (e.g., arginine, glutamate, glutamine, glycine, and proline) for animals to achieve their full genetic potential for growth, development, reproduction, lactation, and resistance to metabolic and infectious diseases. This concept represents a new paradigm shift in protein nutrition to guide the feeding of mammals (including livestock), poultry, and fish. (Supported by USDA-NIFA grants)